Efeito do laser de baixa intensidade (830nm) associado ao exercício em ratos obesos exógenos - Aquino Junior, Antonio Eduardo de (2012)
Obesity is a multifactorial disease that has endogenous and exogenous origin and this includes 95% of all cases. One of the treatments takes into account the negative energy balance, which is the relationship between decreasing consumption and increased caloric expenditure. The aim of this study was to evaluate the systemic effects of low intensity laser associated the moderate exercise of swimming in obesity animals exogenous. Male Wistar rats were randomly distributed in eight groups (N=64). SC (sedentary chow-diet) SCL (sedentary chow-diet laser), EC (exercised chow-diet), ECL (exercised chow-diet laser), SH (sedentary high-fat diet), SHL (sedentary highfat diet laser), EH (exercised high-fat diet) and EHL (exercised high-fat diet laser). The exercise protocol followed parameters of Damaso, 1996. The irradiation parameters was 100mW, 60mW/cm2,and the Treatment time was 47s applied to both hind feet of the animals immediately after the exercise. Significant differences were found in groups with association between laser and exercise, in special the biochemical parameters (total cholesterol, triglycerides and LDL) as well as modification of the adipocytes area by morphometric analysis. The advent of new possibilities in the treatment of obesity and associated diseases such as dyslipidemia is crucial upon the pattern of eating behavior that modern society is willing to use. The therapy show to be a possible additional tool in treatment of obesity.